2019
DOI: 10.1039/c9cc03909k
|View full text |Cite
|
Sign up to set email alerts
|

A new mitochondrion targetable fluorescent probe for carbon monoxide-specific detection and live cell imaging

Abstract: A red molecular probe for carbon monoxide (CO)-specific detection based on palladium-free mediated opening of spirolactam has been applied to establish a safe and powerful method to detect and image CO changes in biological systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…Many palladium-based probes have been reported with greater sensitivity for CO than the ruthenium-based system reported here. [8,10] However, concerns remain over the toxicity of Pd II salts [11] in living systems and the slow response time caused by the need for diffusion controlled co-location of three reaction partners (Pd salt, fluorophore and CO) for detection to occur. Our probe is the only competitive metalbased system not based on palladium and successfully addresses both of these issues.…”
Section: Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many palladium-based probes have been reported with greater sensitivity for CO than the ruthenium-based system reported here. [8,10] However, concerns remain over the toxicity of Pd II salts [11] in living systems and the slow response time caused by the need for diffusion controlled co-location of three reaction partners (Pd salt, fluorophore and CO) for detection to occur. Our probe is the only competitive metalbased system not based on palladium and successfully addresses both of these issues.…”
Section: Communicationsmentioning
confidence: 99%
“…[8][9][10] These processes are slow at 37 8C, leading to long response times (commonly > 40 min), and use potentially cytotoxic, non-ligated heavy metal salts or require addition of significant amounts of organic co-solvents. [7][8][9][10][11] There is a pressing need for sensitive, selective, rapid and reliable fluorescent CO probes which overcome the limitations listed above.…”
mentioning
confidence: 99%
“…Due to the conversion of electron withdrawing aryl nitro group to electron releasing aryl amino group, turn on fluorescence occurs and the process is non‐toxic as well as having nominal cost . Beside this a lanthanide based system showing turn‐on fluorescence in the presence of CORM‐3, spirolactam ring opening in the presence of CORM‐3 resulting turn‐on fluorescence, is also reported recently and the mechanistic discussion of these reports are depicted on the respective sections.…”
Section: Introductionmentioning
confidence: 69%
“…Further, fluorescence imaging of exogenous CO in HepG2 cells, endogenous CO produced via heme stimulation, subsequently increases the activity of heme oxygenase which increases the concentration of CO by breaking hemoglobin, unequivocally established the applicability of the probe in biology (Figure 28). [30] Zhang et al reported fluorescent probe Mito-Ratio-CO to detect CO in mitochondria over other various bioactive molecules. Mito-Ratio-CO itself has a blue emission, when CO and Pd 2 + together caused a cleavage to produce Mito-Ratio-OH, which augmented the ICT process.…”
Section: Fluorescent Probes For Mitochondrial-targetable Co Detectionmentioning
confidence: 99%
“…In addition to the three mechanisms for detecting CO described above, Zhou et al reported a novel recognition site in 2019. 74 As shown in Fig. 8, the probe 55 was designed by incorporating 2-(hydrazonomethyl)-pyridine as a CO-responsive group in lactam form.…”
Section: Other Mechanismsmentioning
confidence: 99%